Generation of baroclinic tides over an isolated underwater bank. Issue 9 (13th September 2013) - Vlasenko, Vasiliy; Stashchuk, Nataliya; Palmer, Matthew R.; Inall, Mark E.
<x xml:space="preserve">Abstract</x> [1] The interaction of stratified tidal flow with an isolated bank (Jones Bank in the Celtic Sea) was investigated numerically and using observational data collected during the 25th research cruise of the R/V James Cook in July 2008. Two scenarios of observed wave generation, one with pure tidal forcing and another with an extra background current, were reproduced numerically and compared against the observational data. It was found that the tidal currents alone produced subcritical conditions for the first‐mode internal wave generation and supercritical flow for the second‐mode waves. Under these conditions, the first‐mode waves with amplitudes up to 10 m freely radiated from the bank, gradually transforming into attenuating dissipative baroclinic bores. Due to supercritical conditions, the second‐mode waves were arrested at the lee side of the bank for 3 h where they grew in amplitude (up to 35 m) and after their release propagated as a series of second‐mode internal solitary waves. The additional background current that was measured near the bank in the middle of June 2008 radically changed the conditions of wave generation. A strong southeastern current arrested the first‐mode perturbations at the NE flank of the bank for 2 h, where they grew in amplitude to almost 40 m and disintegrated into packets of first‐mode internal solitary waves after their release. For the second‐mode perturbations, the flow was substantially supercritical for more than one fourth of a tidal period so that these waves were just washed away from the generation site without any visible amplification.